Detection of Indonesian Food to Estimate Nutritional Information Using YOLOv5 - Gina Cahya Utami; Chyntia Raras Widiawati; Pungkas Subarkah (Teknika, 2023)
Currently, the development of online food delivery service applications is very popular. The application offers convenience in finding and fulfilling food needs. That circumstance has an impact such as not controlling the type and amount of food consumed. Therefore, to maintain a healthy lifestyle, people need to eat healthy and nutritious food. The goal of this research is to build a model using the YOLOv5 model that can detect images of Indonesian food so that nutritional estimation can then be carried out by taking information per serving data sourced from the FatSecret Indonesia website. The methods of this research include data collection, data pre-processing, training, testing, evaluation, image detection, and model export. The outcome of this research is an object detection model that is ready to be implemented in android applications or websites to detect images of Indonesian food which can be estimated for each nutrient. Based on the detection results, 98.6% for an average of a curacy, 95% for precision, 95.3% for recall, and 95% for F1-Score were obtained. The results of the detection are then used to estimate nutrition by taking information per portion from the FatSecret Indonesia website. From the experiments that were carried out on seven pictures of Indonesian food, the estimation was carried out well by displaying various nutritional information including energy, protein, fat, and carbohydrates.